Women’s autonomy and its effect on antenatal care visits among Tharu women of reproductive age (15-49) of Khairahani Municipality, Nepal - Adhikari, Anuska; Kaphle, Maheshor (Journal of Health Promotion, 2022)
Women’s autonomy in health care decision-making is enormously essential for improved maternal and child health outcomes and women’s empowerment. This study examines women’s autonomy and its effect on antenatal care (ANC) visits among the women of the Tharu community of Khairahani municipality, Chitwan. The probability proportional to size (PPS) sampling technique was adapted for sample estimation in each selected ward. A list of all the Tharu households in the community was prepared from which 294 women were selected using systematic random sampling techniques. Univariate, bivariate (Chisquare test), and multivariate analyses (binary logistic regression) were performed. One-fifth of women were youths aged 15-24 (mean 27.8 years). One out of ten women was illiterate, and about two-thirds (65%) were involved in agriculture. More than two in five women (42%) did not have autonomy. Women’s autonomy, age group, educational status, occupational status, and husband’s occupational status were significantly associated with antenatal care visits. A significantly high number of women (p<0.001) who had high autonomy (89%), compared with those who had no autonomy (65%), used ANC services for their last birth. Women with low autonomy and high autonomy were three times (OR=3.05; 95% CI=1.01-8.5) and 4.5 times (OR=4.5; 95% CI 2.3-8.6) more likely to utilize ANC visits than those who had no autonomy. Women’s autonomy in healthcare decision-making, household purchases, and money expenditure were significantly associated with the use of antenatal care visits. Women’s participation in the decision-making process regarding health care and household matters should be focused on and increased for better utilization of antenatal care services.